Structural basis of retinal membrane guanylate cyclase regulation by GCAP1 and RD3 - Ames, James B. (Frontiers in Molecular Neuroscience, 2022)
Retinal membrane guanylate cyclases (RetGC1 and RetGC2) are expressed in photoreceptor rod and cone cells, where they promote the onset of visual recovery during phototransduction. The catalytic activity of RetGCs is regulated by their binding to regulatory proteins, guanylate cyclase activating proteins (GCAP1-5) and the retinal degeneration 3 protein (RD3). RetGC1 is activated by its binding to Ca2+-free/Mg2+-bound GCAP1 at low cytosolic Ca2+ levels in light-activated photoreceptors. By contrast, RetGC1 is inactivated by its binding to Ca2+-bound GCAP1 and/or RD3 at elevated Ca2+ levels in dark-adapted photoreceptors. The Ca2+ sensitive cyclase activation helps to replenish the cytosolic cGMP levels in photoreceptors during visual recovery. Mutations in RetGC1, GCAP1 or RD3 that disable the Ca2+-dependent regulation of cyclase activity are genetically linked to rod/cone dystrophies and other inherited forms of blindness. Here I review the structural interaction of RetGC1 with GCAP1 and RD3. I propose a two-state concerted model in which the dimeric RetGC1 allosterically switches between active and inactive conformational states with distinct quaternary structures that are oppositely stabilized by the binding of GCAP1 and RD3. The binding of Ca2+-free/Mg2+-bound GCAP1 is proposed to activate the cyclase by stabilizing RetGC1 in an active conformation (R-state), whereas Ca2+-bound GCAP1 and/or RD3 inhibit the cyclase by locking RetGC1 in an inactive conformation (T-state). Exposed hydrophobic residues in GCAP1 (residues H19, Y22, M26, F73, V77, W94) are essential for cyclase activation and could be targeted by rational drug design for the possible treatment of rod/cone dystrophies.